2022
DOI: 10.3390/s22031009
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Upper Limb Robotic-Assisted Therapy Using the Track-Hold Device

Abstract: The Track-Hold System (THS) project, developed in a healthcare facility and therefore in a controlled and protected healthcare environment, contributes to the more general and broad context of Robotic-Assisted Therapy (RAT). RAT represents an advanced and innovative rehabilitation method, both motor and cognitive, and uses active, passive, and facilitating robotic devices. RAT devices can be equipped with sensors to detect and track voluntary and involuntary movements. They can work in synergy with multimedia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…The robot mechanism is propelled by gravitational and inertial forces. It is equipped with wearable sensors and free‐contact devices for gesture tracking on the wrist, elbow, and shoulder 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…The robot mechanism is propelled by gravitational and inertial forces. It is equipped with wearable sensors and free‐contact devices for gesture tracking on the wrist, elbow, and shoulder 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, robot arms for pick-and-place and assembly tasks have matured [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ], and many factory robot arms now use two- or three-finger grippers for tasks, and many research papers have been conducted in this direction or for experiments [ 9 , 10 , 11 , 12 ]. Some use algorithms for control [ 13 ] and others use visual images and machine learning to allow robotic arms to perform tasks [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al [ 8 , 9 ] developed a passive robotic arm capable of recording and facilitating the movement of the upper extremity to aid in the rehabilitation of the upper extremity after stroke. Another line of scholars [ 10 , 11 ] have suggested that robotic-assisted therapy may help improve arm and function in patients with cervical spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%